Perpetuation of Gender Inequalities in Households: from Culture to Cognition - Deb, Angarika (Journal of cognition and culture, 2024)
Though labor-force participation of women has considerably increased in industrialized societies and many households are now dual-earner, the gender imbalance in household division of labor persists. Moreover, the consensus amongst men and women is that such distributions are fair, resulting in normalization and further perpetuation of inequalities. We provide a multidisciplinary explanation, focusing on the economic, cultural and cognitive processes underlying the perpetuation of inequalities within households. The article begins with a broad, economic approach that details the role of outside options and how they impact available decisions across different subsistence communities. We then discuss the role of cultural narratives and norms in shaping internalized structures of inequality. Finally, we unify these perspectives by focusing on the cognitive mechanisms that underpin self-perception and motivated assessments of fairness within households. We end with a brief discussion on the policy significance and avenues of future work.